2008
DOI: 10.1258/ijsa.2008.008120
|View full text |Cite
|
Sign up to set email alerts
|

Condom ‘turn offs’ among adults: an exploratory study

Abstract: An exploratory study compared the prevalence of multiple types of condom-associated 'turn offs' in men and women. Nearly 2000 people completed a web-based questionnaire. Data were analysed from 464 men and women who reported that condoms had turned them off the last time they were used. Gender differences were not observed for the majority (9) of 15 turn offs. The most common turn offs related to loss of pleasure. For example, more than three-quarters of the men and nearly 40% of the women reported decreased s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
61
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 20 publications
2
61
1
Order By: Relevance
“…53 The interviews and literature review identified a multitude of potential barriers to condom use. 3 Behaviour change techniques l Problem-solving.…”
Section: Rationalementioning
confidence: 99%
See 3 more Smart Citations
“…53 The interviews and literature review identified a multitude of potential barriers to condom use. 3 Behaviour change techniques l Problem-solving.…”
Section: Rationalementioning
confidence: 99%
“…3,57 All data sources identified alcohol as a strong barrier to condom use. The importance of carrying/the availability of condoms has been related to condom use in the literature and lack of availability was identified as a barrier by experts in the workshops.…”
Section: Rationalementioning
confidence: 99%
See 2 more Smart Citations
“…[10][11][12][13][14][15][16] Prior interventions designed to increase correct and consistent condom use have insufficiently addressed these sexual aspects of condom use. In the KIHIS program, the sexual arousal aspects of condom use are emphasized.…”
mentioning
confidence: 99%